Management protocols for status epilepticus in the pediatric emergency room: systematic review article - Cheuk C. Au; Ricardo G. Branco; Robert C. Tasker (Brazilian Society of Pediatrics, 2017)
Objective: This systematic review of national or regional guidelines published in English aimed to better understand variance in pre‐hospital and emergency department treatment of status epilepticus. Sources: Systematic search of national or regional guidelines (January 2000 to February 2017) contained within PubMed and Google Scholar databases, and article reference lists. The search keywords were status epilepticus, prolonged seizure, treatment, and guideline. Summary of findings: 356 articles were retrieved and 13 were selected according to the inclusion criteria. In all six pre‐hospital guidelines, the preferred route of medication administration was to use alternatives to the intravenous route: all recommended buccal and intranasal midazolam; three also recommended intramuscular midazolam, and five recommended using rectal diazepam. All 11 emergency department guidelines described three phases in therapy. Intravenous medication, by phase, was indicated as such: initial phase - ten/11 guidelines recommended lorazepam, and eight/11 recommended diazepam; second phase - most (ten/11) guidelines recommended phenytoin, but other options were phenobarbital (nine/11), valproic acid (six/11), and either fosphenytoin or levetiracetam (each four/11); third phase - four/11 guidelines included the choice of repeating second phase therapy, whereas the other guidelines recommended using a variety of intravenous anesthetic agents (thiopental, midazolam, propofol, and pentobarbital). Conclusions: All of the guidelines share a similar framework for management of status epilepticus. The choice in route of administration and drug type varied across guidelines. Hence, the adoption of a particular guideline should take account of local practice options in health service delivery.